Dual Phosphoinositide 3-Kinase/Mammalian Target of Rapamycin Inhibitor NVP-BEZ235 Has a Therapeutic Potential and Sensitizes Cisplatin in Nasopharyngeal Carcinoma - Yang, Fen; Qian, Xiao-Jun; Qin, Wei; Deng, Rong; Wu, Xiao-Qi; Qin, Juan; Feng, Gong-Kan; Zhu, Xiao-Feng (PloS one, 2013)
Phosphoinositide 3-kinase (PI3K)/AKT/mammalian target of rapamycin inhibitor (mTOR) pathway is often constitutively activated in human tumor cells and thus has been considered as a promising drug target. To ascertain a therapeutical approach of nasopharyngeal carcinoma (NPC), we hypothesized NVP-BEZ235, a novel and potent imidazo[4,5-c] quinolone derivative, that dually inhibits both PI3K and mTOR kinases activities, had antitumor activity in NPC. Expectedly, we found that NVP-BEZ235 selectively inhibited proliferation of NPC cells rather than normal nasopharyngeal cells using MTT assay. In NPC cell lines, with the extended exposure, NVP-BEZ235 selectively inhibited proliferation of NPC cells harboring PIK3CA mutation, compared to cells with wild-type PIK3CA. Furthermore, exposure of NPC cells to NVP-BEZ235 resulted in G1 growth arrest by Propidium iodide uptake assay, reduction of cyclin D1and CDK4, and increased levels of P27 and P21 by Western blotting, but negligible apoptosis. Moreover, we found that cisplatin (CDDP) activated PI3K/AKT and mTORC1 pathways and NVP-BEZ235 alleviated the activation by CDDP through dually targeting PI3K and mTOR kinases. Also, NVP-BEZ235 combining with CDDP synergistically inhibited proliferation and induced apoptosis in NPC cells. In CNE2 and HONE1 nude mice xenograft models, orally NVP-BEZ235 efficiently attenuated tumor growth with no obvious toxicity. In combination with NVP-BEZ235 and CDDP, there was dramatic synergy in shrinking tumor volumes and inducing apoptosis through increasing Noxa, Bax and decreasing Mcl-1, Bcl-2. Based on the above results, NVP-BEZ235, which has entered phase I/II clinical trials in patients with advanced solid tumors, has a potential as a monotherapy or in combination with CDDP for NPC treatment.